Effect of Nb on microstructure and corrosion resistance of X80 pipeline steel. (June 2023) - Xia, Fan; Li, Zhiwei; Ma, Ming; Zhao, Yonggang; Wu, Changjun; Su, Xuping; Peng, Haoping
Abstract: In this study, a series of χNb-X80 pipeline steels were obtained by adding different contents of Nb to X80 pipeline steel and after different cooling rates. The effects of Nb on the microstructure and corrosion resistance of X80 pipeline steel were studied by metallographic microscope, scanning electron microscope, differential scanning calorimeter, electrochemical corrosion, and salt spray corrosion. The results show that the high cooling rate will hinder the phase transformation, reduce the diffusion ability of Nb element at the grain boundary, inhibit the growth rate of ferrite grains, and refine the grains of the sample steel structure. The grain refinement effect is the best when the cooling rate is 40 °C/min. In addition, the reason why Nb improves the corrosion resistance of X80 pipeline steel is discussed from two aspects: the change of corrosion products and the effect of grain refinement. The analysis shows that Nb promotes the formation of a dense corrosion protective film, and this positive effect of the protective film overcomes the negative corrosion effect caused by the grain refinement caused by the precipitated Nb (CN), thereby enhancing the corrosion resistance of the substrate. The corrosion resistance is the best when the Nb content is 0.16 wt %. Highlights: The higher the cooling rate, the smaller the grain size of the sample steel and the more uniform distribution of the metallographic structure. The optimum cooling rate is 40 °C/min. Appropriate addition of Nb is beneficial to promote the formation of dense corrosion product layer and improve the corrosion resistance of X80 pipeline steel. The solid solution strengthening and precipitation of Nb(CN) refine the grains of the X80 pipeline steel structure.